Long-term efficacy of clinical hunger provocation to wean feeding tube dependent children. Issue 9 (September 2020) - Krom, Hilde; de Meij, Tim G.J.; Benninga, Marc A.; van Dijk-Lokkart, Elisabeth M.; Engels, Michelle; Kneepkens, C.M. Frank; Kuiper-Cramer, Liesbeth; Otten, Marie-Anne G.M.; van der Sluijs Veer, Liesbeth; Stok-Akerboom, Anita M.; Zilverberg, Riëtte; van Zundert, Suzanne M.C.; et al.
Summary: Background & aims: The incidence of tube feeding dependency seems to increase worldwide, and these children may remain on prolonged tube feeding for many months to years. The multidisciplinary clinical hunger provocation (CHP) program is an intensive inpatient intervention of usually 2–3 weeks, aimed at weaning children from tube feeding. CHP has been proven highly effective on the short term (80–86%), particularly when applied before the age of two years but long-term data are lacking. The aims of our study were to determine the long-term efficacy of the CHP program and factors associated with success or failure and to assess anthropometrics, feeding behavior, and medical outcomes at long-term follow-up. Methods: All tube-dependent children who underwent CHP at a tertiary hospital in Amsterdam, the Netherlands, between 2001 and 2014, and had a minimum follow-up of 12-months in 2015, were eligible to participate in this retrospective cohort study. During the CHP program, tube feeding is ceased stepwise to create appetite, according to a strict protocol. The program was defined successful if patients achieved oral intake and could be fully weaned from tube feeding following the CHP program. Acute malnourishment was defined as weight for height <2 SD or loss of >1 SD within 3 months, chronic malnourishment as height for age <2 SD and both acute and chronic malnourishment as both a height for age and weight for height <2 SD. Long-term efficacy (tube free at varying follow-up periods), anthropometrics (height for age, weight for height), feeding behavior and medical outcomes were assessed by a structured cross-sectional parental interview. Results: In total, 57 patients were admitted to the CHP program. Fifty-two patients could be contacted of whom 42 participated in the study (response rate 81%) with a median age at admittance of 19 (IQR 13–22) months (62% female). The program was initially successful in 36/42 (86% (Bca CI 95% 75.0–95.2)) patients. A younger age upon initiation of tube feeding was negatively correlated with success ( p 0.016). At follow-up, a median period of 67.0 (IQR 37.0–101.5) months after discharge, long-term efficacy was 32/41 (78% (Bca CI 95% 64.1–90.0)) (1 missing data). Patients with a successful CHP had beneficial outcomes compared to those with an unsuccessful CHP, showing less selective eating behavior ( p 0.025), nocturnal feeding ( p 0.044), forced feeding ( p 0.044) and hospital admissions ( p 0.028). However, 44% of successfully weaned patients fulfilled the criteria for malnourishment at long-term follow-up (13% acute, 22% chronic, and 9% both acute and chronic (compared to 22% at admittance: 13% acute, 6% chronic, and 3% both)). 59.4% of successfully weaned patients showed signs of developmental delays or were diagnosed with new medical diagnoses (43.8%) at long-term follow-up. Conclusions: The multidisciplinary CHP is a highly effective short-term (86%) and long-term (78%) intervention to wean young children from tube feeding, with beneficial feeding outcomes. However, at long-term follow-up, many successfully weaned patients were malnourished, showed signs of developmental delay, and were diagnosed with new medical diagnoses. For these reasons, patients should be monitored carefully during and after tube weaning, also after successful CHP. Tube dependency might be an early expression of medical diagnoses.